2022
DOI: 10.7717/peerj.13376
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol alleviates liver fibrosis by inducing endoplasmic reticulum stress-mediated necroptosis of hepatic stellate cells through Sirt1/NICD pathway

Abstract: Liver fibrosis is a repair response process after chronic liver injury. During this process, activated hepatic stellate cells (HSCs) will migrate to the injury site and secrete extracellular matrix (ECM) to produce fibrous scars. Clearing activated HSCs may be a major strategy for the treatment of liver fibrosis. Curcumol isolated from plants of the genus Curcuma can effectively induce apoptosis of many cancer cells, but whether it can clear activated HSCs remains to be clarified. In the present study, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…AML12 cells treated with or without Ac2-26 were stained in 0.4% trypan blue in phosphate buffered saline (PBS) for 3 min, washed two times with PBS, and then observed under a phase-contrast microscope (Leica Microsystems, Germany) ( Sun et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…AML12 cells treated with or without Ac2-26 were stained in 0.4% trypan blue in phosphate buffered saline (PBS) for 3 min, washed two times with PBS, and then observed under a phase-contrast microscope (Leica Microsystems, Germany) ( Sun et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“… 118 Curcumol is an effective active ingredient extracted from the genuine medicinal herb Curcuma kwangsiensis S. G. Lee et C. F. Liang in Guangxi, China, which is known for its ability to invigorate blood circulation and remove blood stasis, protect the liver, and have anti-inflammatory, cholagogic and antioxidant effects. 119 , 120 Curcumol inhibits miR-125b/NLRP3 pathway to prevent liver fibrosis. Mechanistically, it can upregulate the expression of miR-125b, which decreases the downstream NLRP3 inflammasome and the expression of Caspase-1, GSDMD, IL-1β, and IL-18, reduces the onset of pyroptosis, and inhibits the activation of HSC to prevent liver fibrosis.…”
Section: Traditional Chinese Medicine and Its Active Ingredients Infl...mentioning
confidence: 99%
“…Fifth, it has been found that the effect of curcumin in the treatment of LF is to remove activated HSCs by inducing necrosis of HSCs. In terms of mechanism, curcumin induces endoplasmic reticulum stress-mediated necrotic prolapse of HSCs through the Sirt1/NICD pathway to attenuate LF [200] . Moreover, curcumin downregulates the Smad pathway and reduces HSC activation in experimental fibrosis [190] .…”
Section: Curcuminmentioning
confidence: 99%